COMPARATIVE ANALYSIS BUILDING SEISMIC EVALUATION USING CONCRETE FRAMES AND REINFORCED MASONRY WALL IN ISLAMIC SCHOOL - Gazali, Abdhy; Aulia, Rahmi; Nurrahmawati, Annisa; Noruza, Egi (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2025)
Existing school buildings in high-seismic regions may not comply with current seismic provisions, increasing the risk of severe damage during earthquakes. This study evaluates the seismic performance of an Islamic School building in Bogor, West Java, and examines how the assumed structural system—Concrete Moment Frame (C1) versus Reinforced Masonry (RM1)—affects ASCE 41-17 evaluation outcomes. The work combines document review, field investigation, 3D ETABS modelling, and Tier 1–Tier 2 assessments under the BPOE target (Life Safety at BSE-1E and Collapse Prevention at BSE-2E).  For the C1 assumption, Tier 1 screening identified several non-compliant checklist items and shear demand–capacity ratios exceeding unity: 1.61 for BSE-1E and 1.57 for BSE-2E.  Tier 2 (linear dynamic, displacement-controlled) results further showed column acceptance exceedances, with m-factor D/C ratios reaching about 3 under BSE-1E and about 4.5 under BSE-2E.   After reclassifying the system as RM1 to better represent the as-built behaviour, the primary wall shear D/C ratios fell below 1 (0.63 for BSE-1E and 0.46 for BSE-2E), indicating adequate lateral capacity.  These findings highlight that correct structural-system identification is critical for meaningful seismic evaluation, and targeted retrofit measures (e.g., FRP strengthening of critical elements) are recommended to enhance safety.